A Urologist's Guide to Ingredients Found in Top-Selling Nutraceuticals for Men's Sexual Health. (1st November 2015) - Cui, Tao; Kovell, Robert C.; Brooks, David C.; Terlecki, Ryan P.
Abstract: Introduction: Use of supplements is common among men seeking urologic evaluation for sexual health matters. With a dizzying array of formulations available and little regulation on the dosage, purity, or ingredients found in these products, the health effects of nutraceuticals are often confusing to patients and medical practitioners alike. Aim: In this review, we set out to concisely summarize the data on ingredients found within the top-selling nutraceutical agents marketed for men's sexual health in order to provide a clinical guide for urologists. Methods: We used sales data from the most popular retail provider of men's health supplements to identify the top-selling products marketed toward improvement of men's sexual health. We summarized the available information related to the ingredients, dosage, cost, and mechanism of action for these substances and performed an extensive literature search to identify and review the current evidence available for each of the most common ingredients found in these nutraceuticals. Results: The top-selling nutraceuticals marked for men's sexual health contain a blend of multiple supplements (up to 33 in one formulation identified), the most common being ginseng, tribulus, zinc, horny goat weed, B complex vitamins/trace minerals, fenugreek, L-arginine, maca, DHEA, ginkgo, and yohimbine. The currently available medical literature evaluating the efficacy of these substances is generally of low quality. Conclusions: Despite the dearth of evidence supporting nutraceutical agents in the men's health arena, these substances are still commonly used by patients. As these products can affect the health and well-being of men presenting to a urology clinic, a familiarity with commonly used agents can help the urologist appropriately counsel their patients.